2018
DOI: 10.1088/1361-665x/aac43d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting parameters on strain hardening of nickel–titanium shape memory alloy

Abstract: Nickel–titanium shape memory alloy (SMA) has been widely used as implant materials due to its good biocompatibility, shape memory property and super-elasticity. However, the severe strain hardening is a main challenge due to cutting force and temperature caused by machining. An orthogonal experiment of nickel–titanium SMA with different milling parameters conditions was conducted in this paper. On the one hand, the effect of cutting parameters on work hardening is obtained. It is found that the cutting speed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This is a consequence of flank wear ( Figure 5b) of cutting tool at high temperature because the friction coefficient increases with cutting speed [40][41][42][43][44][45][60][61][62][63][64][65]. An improvement in surface roughness due to the increase in cutting speeds is an expected result [65][66][67][68][69][70][71][72][73][74]. The increase in surface roughness at high cutting speed (50 m/min) and feed rate (0.14 mm/tooth) was attributed to the high tool wear on the cutting tool ( Figure 4c).…”
Section: Change In Surface Roughness Due To Cutting Speed and Feed Ratementioning
confidence: 99%
“…This is a consequence of flank wear ( Figure 5b) of cutting tool at high temperature because the friction coefficient increases with cutting speed [40][41][42][43][44][45][60][61][62][63][64][65]. An improvement in surface roughness due to the increase in cutting speeds is an expected result [65][66][67][68][69][70][71][72][73][74]. The increase in surface roughness at high cutting speed (50 m/min) and feed rate (0.14 mm/tooth) was attributed to the high tool wear on the cutting tool ( Figure 4c).…”
Section: Change In Surface Roughness Due To Cutting Speed and Feed Ratementioning
confidence: 99%
“…The scanning electron microscope (SEM) image of the BUE formed on the cutting tool at 20 m/min Vc is shown in Figure 7a. The BUE forming on the cutting tool increases the cutting tool rε and contributes positively to the Ra value [14,21,22]. Increasing the Vc from 20 to 35 m/min increased the Vc and the Ra.…”
Section: Effects Of Cutting Parameters On Average Surface Roughnessmentioning
confidence: 97%
“…As a result of the experimental studies, the researchers determined that the most important parameter affecting the work hardening was the cutting speed (V c ). When the effect of the feed rate (f z ) on the work hardening was examined, they observed that work hardening increased with the increase in the f z [14]. Guo et al analyzed the surface integrity of the alloy due to tool wear, burr formation, and the formation of a white layer on the workpiece surface during the processing of NiTi SMA by milling and the electro discharge machining (EDM) method.…”
Section: Introductionmentioning
confidence: 99%
“…The most important effects of these deformations are the strain hardening of the surface layers. Since these plastic deformations affect the service life of the final product, various researches have been conducted in this field [1][2][3][4][5][6][7][8][9][10][11][12], in these studies, the effects of machining parameters on strain hardening in the surface layers of the machined workpiece has been investigated experimentally and theoretically. In some materials, work hardening adversely affects the machining process, and consequently, the temperature and machining forces increase during the cutting operation.…”
Section: Introductionmentioning
confidence: 99%